Applicability study of the potting material based thermal management strategy for permanent magnet synchronous motors. (25th February 2019) - Sun, Yalong; Zhang, Shiwei; Yuan, Wei; Tang, Yong; Li, Jingrong; Tang, Kairui
Highlights: Silicon gelatin encapsulation is systematically studied for PSMS thermal management. The P-M shows a lower stable operation temperature at any working condition. Potting silicon gelatin increases heat transfer pathway and temperature uniformity. The P-M can twofold extend the stable running time under the peak-load condition. Abstract: The evolution from traditional internal combustion engine cars to the new energy vehicles has promoted the rapid development of the permanent magnet synchronous motors (PMSMs) with ever increasing performance requirements. The heat dissipation capability of the PMSMs, as one of the most important factors for the stable operation of the PMSMs, has attracted wide attentions while still remains to be properly solved. In this paper, potting silicon gelatin was encapsulated in the gaps between the end windings and the casing of PMSMs as an enhanced thermal management strategy. The systematic temperature rise tests showed that the PMSMs with potting silicon gelatin (P-M) had a lower stable operation temperature than the original PMSMs (O-M) at any working condition when the same cooling conditions were applied, and the maximum temperature decrease reached 27.3 °C, which was 23.6% lower than the O-M. Furthermore, the stable operation time of the P-M under the peak-load condition has been about twofold extended with an improvement from 84 s to 165 s. In addition, a computational fluid dynamics (CFD) model was used to illustrate the temperature distribution of the motors, which showed good consistency with the test results and predicted the stable running time accurately under the peak-load condition.